Abnormal junctions between surface membrane and sarcoplasmic reticulum in skeletal muscle with a mutation targeted to the ryanodine receptor. - Takekura, H (1995)
Junctions that mediate excitation-contraction (e-c) coupling are formed between the sarcoplasmic reticulum (SR) and either the surface membrane or the transverse (T) tubules in normal skeletal muscle. Two structural components of the junctions, the feet of the SR and the tetrads of T tubules, have been identified respectively as ryanodine receptors (RyRs, or SR calcium-release channels), and as groups of four dihydropyridine receptors (DHPRs, or voltage sensors of e-c coupling). A targeted mutation (skrrm1) of the gene for skeletal muscle RyRs in mice results in the absence of e-c coupling in homozygous offspring of transgenic parents. The mutant gene is expected to produce no functional RyRs, and we have named the mutant mice "dyspedic" because they lack feet--the cytoplasmic domain of RyRs anchored in the SR membrane. We have examined the development of junctions in skeletal muscle fibers from normal and dyspedic embryos. Surprisingly, despite the absence of RyRs, junctions are formed in dyspedic myotubes, but the junctional gap between the SR and T tubule is narrow, presumably because the feet are missing. Tetrads are also absent from these junctions. The results confirm the identity of RyRs and feet and a major role for RyRs and tetrads in e-c coupling. Since junctions form in the absence of feet and tetrads, coupling of SR to surface membrane and T tubules appears to be mediated by additional proteins, distinct from either RyRs or DHPRs.